Examining self-regulation in the preschool years: Links to psychosocial outcomes, maternal adverse childhood experiences, and parental emotion regulation - Daniel, Samantha (My University, 2020)
Self-regulation (SR), which refers to the ability to regulate one’s own behaviour, emotions, and thoughts, is an important developmental milestone that impacts an array of outcomes throughout the lifespan. The purpose of the current study was to examine how SR is related to theoretically linked constructs among preschool-aged children. Based on previous research, several parental factors, including maternal adverse childhood experiences (ACEs), maternal emotion regulation (ER), and paternal SR, were investigated to determine how they impacted child SR. As well, child SR was investigated as a factor that may impact externalizing and internalizing difficulties. The current study represents cross-sectional data from a larger longitudinal research project focused on mothers and their young children. The final sample consisted of 93 mothers and three-year-old offspring. Based on the literature, three mediation models were tested using structural equation modelling: 1) maternal ER was hypothesized to mediate the relation between maternal ACEs and child SR, 2) child SR was hypothesized to mediate the relation between maternal ACEs and child externalizing difficulties, and 3) child SR was hypothesized to mediate the relation between maternal ACEs and child internalizing difficulties. Main effects between these variables were also investigated. A sub-study focused on paternal SR with 47 fathers was also conducted with the same families. Using paternal data, hypotheses were explored that were related to how paternal regulatory variables (including difficulties managing behaviours and emotions) were related to child SR. As well, the impact of paternal and maternal ER was compared for the outcome of child SR. Overall, results of the mediation models were not significant, however there were notable main effects in the maternal and child data. Specifically, maternal ACEs significantly predicted child SR and externalizing difficulties, even after accounting for covariates, indicating that maternal ACEs appear to an important risk factor for specific child outcomes. As well, in the paternal data, there was a significant relationship between paternal SR and child SR, such that fathers who reported difficulty regulating their emotions and behaviours were more likely to have children that demonstrated difficulty with SR. The remaining paternal hypotheses were not significant. Collectively, these results point to maternal ACEs and paternal SR difficulties as factors that appear to increase risk for young children. Given that difficulties with both child SR and externalizing difficulties are associated with persistent negative outcomes, it will be imperative to continue to examine the sequelae associated with maternal ACEs, as well as to evaluate the effectiveness of interventions targeting difficulties associated with maternal ACEs and paternal SR.